2019
DOI: 10.1149/2.0421908jes
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intermittent Operation on Lifetime and Performance of a PEM Water Electrolyzer

Abstract: The aim of this study is to provide a better understanding of performance degrading mechanisms occurring when a proton exchange membrane water electrolyzer (PEM-WE) is coupled with renewable energies, where times of operation and idle periods alternate. An accelerated stress test (AST) is proposed, mimicking a fluctuating power supply by operating the electrolyzer cell between high (3 A cm −2 geo) and low current densities (0.1 A cm −2 geo), alternating with idle periods during which no current is supplied and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
177
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(185 citation statements)
references
References 45 publications
7
177
1
Order By: Relevance
“…Note that the here advanced hypothesis is different from that proposed by Cherevko et al , who on the basis of half‐cell experiments in an aqueous sulfuric acid electrolyte proposed that the intrinsic dissolution rate of hydrous iridium oxide is higher than that of crystalline IrO 2 . Owing to the high iridium loading in the here shown OCV‐AST, the effect of iridium dissolution on the OER activity is very small (< 20 mV ) and the vast majority of the observed performance losses after 718 OCV‐AST cycles (red diamonds Fig. b) are due to an increase of the HFR (red diamonds Fig.…”
Section: Screening Of Oer Catalyst Activity and Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the here advanced hypothesis is different from that proposed by Cherevko et al , who on the basis of half‐cell experiments in an aqueous sulfuric acid electrolyte proposed that the intrinsic dissolution rate of hydrous iridium oxide is higher than that of crystalline IrO 2 . Owing to the high iridium loading in the here shown OCV‐AST, the effect of iridium dissolution on the OER activity is very small (< 20 mV ) and the vast majority of the observed performance losses after 718 OCV‐AST cycles (red diamonds Fig. b) are due to an increase of the HFR (red diamonds Fig.…”
Section: Screening Of Oer Catalyst Activity and Stabilitymentioning
confidence: 99%
“…b), where the anode potential was always kept positive of 1.3 V RHE . Both the increase in HFR as well as the formation of a hydrous Ir(OH) x phase clearly shown by cyclic voltammetry are both related to cycling the anode potential between ≈ 0 V RHE during the OCV‐periods and high potentials when current is applied to the electrolyzer. The main cause for an increasing HFR along with the observed performance decrease over the course of the OCV‐AST can be related to the formation of an additional interfacial resistance on the anode side of the MEA.…”
Section: Screening Of Oer Catalyst Activity and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This will have implications in a commercial sense for electrolysers that are connected to intermittent renewable energy sources that may be subjected to rapid start up and shut down conditions. It has been shown that a reverse current can flow in the electrolyser if a base level of power is not provided . This has significant implications for the stability of the anode.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that a reverse current can flow in the electrolyser if a base level of power is not provided. [86][87] This has significant implications for the stability of the anode. This degradation in performance may be related to structural transitions such as this occurring during reverse current flow in the electrolyser.…”
Section: Resultsmentioning
confidence: 99%